The ‘Ting-ting Game’ as Psychology Intervention to Mitigate Vowel Reading Skill among Remedial Pupils - Muhammad Asyraf Norli, Nor Azwahanum Nor Shaid (Journal for ReAttach Therapy and Developmental Diversities, 2023)
Introduction: Education in Malaysia has undergone various changes. However, problems in basic skills such as reading, writing, and counting still need to be improved. Therefore, every primary school under Malaysian Ministry of Education holds the Special Remedial Program. This program is essential, and remedial pupils' development needs to be emphasized. The ability of a teacher to plan an effective intervention in line with technological progress is vital. In addition, the learning atmosphere can not only improve the performance of remedial pupils, but it is fun and provides memories that remain in the memory of remedial students for a long time. Therefore, an innovation as an intervention is carried out. The effectiveness of invention that uses ‘Ting-Ting Game’ games in students’ learning has been analysed and studied. Objectives: This paper conducted to identifying the level of mastery of Malay language vowel skills among remedial students before using the ‘Ting-Ting Game’, identifying the level of effectiveness of the ‘Ting-Ting Game’ in improving the vowel skills of Remedial Malay Language among remedial pupils and explaining teaching reflection using the ‘Ting-Ting Game’ in improving the vowel skills of the Remedial Malay Language among remedial pupils. Methods: This action research uses qualitative method. Therefore, worksheets, pre-post-tests, field notes and observation checklists were analysed descriptively. Before conducting the study, all instruments were validated by expert, and a pilot study was conducted. Worksheets are to support pre-post-tests. The results of the analysis of worksheets and tests will be compared to prove the effectiveness of the intervention. The worksheet is supported by observational findings using a structured observational checklist. Then, the teaching checklist is also used as a support for the effectiveness of interventions and improvements to the implementation of teaching by teacher. Field note are used as a supporting document. Purposive sampling was used to identify the participants. Three remedial pupils were involved because they met the purpose and the characteristics of the study that had been set. The research data has been analysed and presented in the form of data to facilitate descriptive explanation. Results: The mastery level of study participants in vowel skills before the intervention was at a very weak mastery level. This is proven by the test analysis, which shows that all study participants do not have high scores and show a fragile level of mastery. Using a checklist, the researcher observed that an increase in mastery occurs among pupils from the first action to the last. The analysis of field notes also shows an increase in positive themes that show the effectiveness of the ‘Ting-Ting Game’ in increasing Remedial Malay language vowel skills recovery from the first act to the last act. As a reflection of the teacher, the researcher found that the ‘Ting-Ting Game’ can increase remedial students' mastery of vowel skills and motivation to learn, and classroom management is more organized. In addition, teachers are also more confident and can carry out teaching smoothly. Data have shown that the ‘Ting-Ting Game’ effectives is on the moderate level and can be fixed occasionally. For better result, teacher must conduct the intervention more than one action circle. Conclusions: Using the ‘Ting-Ting Game’ game makes students more enthusiastic about mastering vowel skills. The ‘Ting-Ting Game’ must be used appropriately and improved occasionally to impact the remedial pupils. This traditional game also strengthens the teacher's pedagogy and expands the teaching method to attract more interest. The innovation of this conventional game proves that teaching and learning can create a more cheerful atmosphere and give pupils meaningful memories. Keywords: remedial pupils, vowels skill, Malay Language.